2015
DOI: 10.24264/lfj.15.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Children's Plantar Pressure Distribution with Varied Angle of Hallux

et al.

Abstract: ABSTRACT. Fashion shoes with narrow and tight toe are widely designed for children and their influence was rarely considered. Therefore, the aim of this study is to investigate children's plantar pressure distribution with varied angle of hallux (AoH), so as to simulate the effect of the tight shoes on the children's feet. Totally, 892 healthy children aged between two and 11 were recruited and those with the foot deformities were excluded by an experienced clinical expert. Both the dynamic AoH and plantar pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 13 publications
1
9
0
7
Order By: Relevance
“…În contrast, grupa TD a arãtat cã, dupã o perioadã scurtã de poziþionare în valgus în zona cãlcâiului, COP s-a deplasat rapid spre partea lateralã ºi în cele din urmã a ajuns în poziþia valgus în faza de desprindere a degetelor, aceastã tendinþã fiind confirmatã în studiul lui Zhou ºi colab. [23].…”
Section: Discuþiiunclassified
“…În contrast, grupa TD a arãtat cã, dupã o perioadã scurtã de poziþionare în valgus în zona cãlcâiului, COP s-a deplasat rapid spre partea lateralã ºi în cele din urmã a ajuns în poziþia valgus în faza de desprindere a degetelor, aceastã tendinþã fiind confirmatã în studiul lui Zhou ºi colab. [23].…”
Section: Discuþiiunclassified
“…Analizând distribuþia presiunii plantare, au constatat o presiune mai mare în zona centralã medianã pentru deformarea de tip valgus, însoþitã de o rotire a antepiciorului spre exterior. Aceºtia au mai sugerat cã, spre deosebire de copiii cu dezvoltare normalã, al cãror corp se aflã în dezechilibru dinamic ºi devine stabil în faza de sprijin dublu, din cauza muºchilor slãbiþi la nivelul membrelor inferioare, centrul de greutate al corpului s-a situat mai jos la copiii cu PC ºi s-a consumat mai mult timp în faza de sprijin dublu pentru a redobândi echilibrul [13]. În contrast, la grupa TD s-a observat cã dupã o scurtã perioadã de poziþionare a cãlcâiului în valgus, centrul de presiune s-a deplasat rapid în lateral ºi s-a poziþionat în valgus la desprinderea degetelor, aceastã tendinþã fiind confirmatã în studiul lui Zhou ºi colab.…”
Section: Discuþii I N T E R M S O F S D C P O U T C O M E S O F F I V Eunclassified
“…By considering the plantar pressure distribution, they found that a higher pressure was obtained at medial midfoot for valgus, accompanied by a forefoot rotated outwards. They further suggested that, unlike the TD child, whose body was in a status of dynamic imbalance and it became stable in the double stance phase, because of the weakened lower limbs muscles, centre of body gravity was lowered in the SDCP children and more time was consumed in the period of double stance phase in order to recover the situation of balance [13]. In contrast, TD showed that after a short period of heel valgus, COP moved fast towards lateral side and finally became valgus in toe off, where its tendency was confirmed in the study of Zhou et al [14].…”
Section: Discuþii I N T E R M S O F S D C P O U T C O M E S O F F I V Ementioning
confidence: 99%
“…Au existat, de asemenea, alte modele de atingere a solului, cu zona centralã ºi cu antepiciorul. Cu toate acestea, 75%-80% dintre alergãtorii de anduranþã ating solul cu retropiciorul [23,24]. În zona centralã, modelul 1 a prezentat cea mai mare forþã maximã, iar presiunea maximã din zona centralã medianã la modelul 1 a fost, de asemenea, cea mai mare.…”
Section: Discuþiiunclassified
“…There were also other striking patterns, which were midfoot striking and forefoot striking patterns. However, 75%-80% of endurance shod runners were rearfoot strikers [23,24]. In the midfoot area, shoe 1 presented the highest max force and the max pressure of shoe 1 in medial midfoot was also the highest.…”
mentioning
confidence: 99%